Implementasi Metode Pembiasaan Puasa Senin Kamis dalam Menguatkan Karakter Disiplin Siswi di Madrasah Tsanawiyah - Supono, Eko; Subando, Joko (Lembaga Yasin AlSys, 2026)
Character education in the perspective of Islamic education occupies a strategic position in shaping the personality of students with noble character, particularly in strengthening the character of discipline. One relevant approach to strengthening the character of discipline is the application of the habituation method of ibadah sunnah (non-obligatory worship), but its implementation in the institutional context of madrasah still needs to be examined in depth. This study aims to comprehensively examine the implementation of the habituation method of Monday and Thursday fasting in strengthening the character of discipline of female students at Madrasah Tsanawiyah Tahfizh Nurul Iman Karanganyar. The study uses a qualitative approach with a descriptive research type, with data collection through observation, interviews, and documentation, which are then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the habituation of Monday and Thursday fasting is carried out in a planned, consistent, and integrated manner with the religious culture of the madrasah, and makes a real contribution to shaping the character of discipline of female students, including time discipline, obedience to rules, behavioral consistency, responsibility, and self-control. The character of discipline that is formed originates from religious awareness so that it is internal and sustainable. This study affirms that the habituation of ibadah sunnah, especially Monday and Thursday fasting, is an effective medium of character education in the context of Islamic education and is relevant to be implemented in madrasah educational institutions.